2003
DOI: 10.1126/stke.2003.167.re2
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Activation in UV-Induced Signal Transduction

Abstract: Experimental evidence supported by epidemiological findings suggests that solar ultraviolet (UV) irradiation is the most important environmental carcinogen leading to the development of skin cancers. Because the ozone layer blocks UVC (wavelength, 180 to 280 nm) exposure, UVA (UVA I, 340 to 400 nm; UVA II, 320 to 340 nm) and UVB (280 to 320 nm) are probably the chief carcinogenic components of sunlight with relevance for human skin cancer. Substantial contributions to the elucidation of the specific signal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
189
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(194 citation statements)
references
References 189 publications
(281 reference statements)
5
189
0
Order By: Relevance
“…These findings are consistent with the existence of distinct responses to UVA and UVB irradiation in keratinocytes. [57][58][59] In summary, this study establishes that CAT gene transfer can prevent a sizable part of the deleterious effects of both UVA and UVB irradiation on normal skin by reduction of UV-induced DNA damage as well as regulation of gene expression or cascade activation via cellular redox modulation. To confirm the effectiveness of CAT overexpression in reduction of UV-induced apoptosis as well as the risk of photocarcinogenesis, the study of xenografted reconstructs on tolerant mice 60 exposed to chronic irradiation as well as clinical trials using topical delivery systems at the protein level are necessary.…”
Section: Discussionmentioning
confidence: 54%
“…These findings are consistent with the existence of distinct responses to UVA and UVB irradiation in keratinocytes. [57][58][59] In summary, this study establishes that CAT gene transfer can prevent a sizable part of the deleterious effects of both UVA and UVB irradiation on normal skin by reduction of UV-induced DNA damage as well as regulation of gene expression or cascade activation via cellular redox modulation. To confirm the effectiveness of CAT overexpression in reduction of UV-induced apoptosis as well as the risk of photocarcinogenesis, the study of xenografted reconstructs on tolerant mice 60 exposed to chronic irradiation as well as clinical trials using topical delivery systems at the protein level are necessary.…”
Section: Discussionmentioning
confidence: 54%
“…Initially characterized by activation of the immediate early genes, c-fos and c-jun and various transcription factors including NFκB (Heck et al, 2004), more recent studies have demonstrated that PI3K/Akt and MAP kinase signaling are also key to the response (Bode and Dong, 2003). We found that MAP kinase and Akt were readily activated by UVB in mouse keratinocytes; however, this response was differentiation-dependent.…”
Section: Discussionmentioning
confidence: 68%
“…Members of the MAPK family are important upstream regulators of transcription factor activities and their signaling is critical to the transduction of a wide variety of extracellular stimuli into intracellular events. The phosphorylation of MAPK molecules controls the activities of various downstream transcription factors implicated in proliferation, differentiation and tumor promotion [46]. ERK1/2 has been shown to be strongly activated by tumor promoters and UV radiation, and has an important role in transmitting signals initiated by them [47].…”
Section: Discussionmentioning
confidence: 99%